Practical realization and adaptation of Cellier's tearing method - Täuber, Patrick; Ochel, Lennart; Braun, Willi; Bachmann, Bernhard (Proceedings of the 6th International Workshop on Equation-Based Object-Oriented Modeling Languages and Tools - EOOLT '14)
This paper is concerned with the tearing method according to François Cellier. Tearing is used to reduce the dimension of algebraic loops, which inevitably arise in the modelling of scientific systems using differential-algebraic equations, as far as possible to achieve an efficient simulation. However, the original tearing method according to Cellier is not suitable for the application in practice, since restrictions on the solvability of equations for variables, and other features, which appear in reality, are not considered. In this work, different changes to the method are introduced and tested, which make it possible to use Cellier Tearing in practice. In addition, the modeller can influence the selection of tearing variables. Modifications of the integrated heuristic are presented, whose efficiency is statistically evaluated at the end of this work. With these changes and the new heuristics, Cellier’s method becomes a very suitable way to optimize the efficiency of simulation in practice.
Keywords: tearing; algebraic loop; simulation performance; tearingSelect; Modelica; OpenModelica